Comparisons of Three Methods for Myopia Control in Adolescents - Ling-fang Du; Fang He; Hua-xia Tan; Na Gao; Wei-qiong Song; Yu-xiu Luo (Journal of Ophthalmology)
Objective. A rising trend in electronic use has increased the prevalence of myopia in adolescents, but the optimal approach to controlling myopia remains undetermined. Here, we explored the effects of common single vision (SV) spectacle lenses combined with 0.01% atropine eye drops (SV + A), orthokeratology (OK) lenses, and peripheral defocus (PD) spectacle lenses on myopia control in adolescents. Methods. Totally 150 myopic adolescent patients (300 eyes) receiving treatment at The First People’s Hospital of Chenzhou City were enrolled. According to doctors’ advice and guardians’ wishes, the patients were divided into SV + A group, OK group, and PD group, with each group consisting of 50 cases (100 eyes). The spherical equivalent, axial length, accommodative response index (accommodative sensitivity and accommodative lag), and intraocular pressure were compared before and after 12 months of wearing lenses, and the complications were recorded. Results. Before wearing lenses, there was no statistical significance in baseline characteristics such as age, gender, and spherical equivalent among the three groups (P>0.05). After wearing lenses, the increase in spherical equivalent and axial length in the SV + A and OK groups were lower than in the PD group (P<0.05), and the SV + A group had the lowest axial length growth. Compared with the SV + A group, accommodative sensitivity was much higher and accommodative lag was significantly lower in the OK and PD groups (P<0.01). In addition, there was no significant difference in intraocular pressure before and after wearing lenses among the three groups (P>0.05). Though the OK group patients had more complications, the difference was not statistically significant (P>0.05). Conclusion. SV + A, OK, and PD lenses can effectively control the progression of myopia in adolescents, but SV + A and OK lenses exhibited more significant effects.